2020
DOI: 10.1186/s12944-020-01303-w
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride is independently correlated with insulin resistance and islet beta cell function: a study in population with different glucose and lipid metabolism states

Abstract: Background: Previous studies on the effects of lipotoxicity and oxidative stress on islet beta cell function mainly focused on patients with diabetes, whereas studies on normal glucose tolerance (NGT) are few. The aim of this study was to explore the relationships among triglyceride (TG), high-density lipoprotein cholesterol (HDL-c), lowdensity lipoprotein cholesterol (LDL-c), oxidative stress indicators, insulin resistance, and beta cell function in populations with different glucose and lipid metabolism stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 56 publications
(55 reference statements)
3
64
0
2
Order By: Relevance
“…After therapy [78] that had a VLCD with a similar therapy duration of six months. The importance of the triglyceride metabolism as presented is further supported by Ma et al [79] and Lim et al [80] who report that triglyceride levels are independently correlated with insulin resistance and islet beta-cell function in individuals with dyslipidemia.…”
Section: Before Therapymentioning
confidence: 61%
“…After therapy [78] that had a VLCD with a similar therapy duration of six months. The importance of the triglyceride metabolism as presented is further supported by Ma et al [79] and Lim et al [80] who report that triglyceride levels are independently correlated with insulin resistance and islet beta-cell function in individuals with dyslipidemia.…”
Section: Before Therapymentioning
confidence: 61%
“…In our study, changes in plasma TG concentrations were correlated to changes in insulin. HTG is associated with metabolic glucose disorders [6,7] and the elevated concentrations of TG levels may lead to peripheral insulin resistance [12]. Subjects with overweight or obesity and HTG of the present study may have more insulin resistance than healthy individuals with overweight or obesity.…”
Section: Discussionmentioning
confidence: 66%
“…In HTG, the elevated concentrations of triglyceride levels may lead to peripheral insulin resistance and islet beta-cell dysfunction [12]. Furthermore, obesity is associated with elevated serum free fatty acids which can contribute to insulin resistance in subjects with obesity [13].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to hyperglycemia without hypertriglyceridemia, a state that may have consequences less severe than those observed with the combined elevation. 26 Zheng T et al, 27 Zheng S et al, 28 Ma M et al, 29 reported that β-cell function was inversely related with TG level and TG promotes β-cell apoptosis. Therefore, lowering of TG level would reduce the β-cell inhibition effect by TG, and that seems to explain why in the present study fasting plasma insulin level was higher in the group with low TG level.…”
Section: Discussionmentioning
confidence: 99%